News. (Computer (00189162), 2015)
Topics include hackers hitting Sony with a devastating attack, a new Bluetooth version offering online connectivity that could advance the Internet of Things, the recent death of the father of the home video-game console, big e-commerce websites crashing under the weight of holiday shopping traffic, lawmakers approving a plan that could break up Google in Europe, advanced malware spying on victims for six years before being discovered, gaming companies worrying that using virtual reality could make players sick, scientists building a molecular-level flash-storage system, researchers saying that many children's apps violate users' privacy, and extensive global law-enforcement operation taking down dark websites.